2013
DOI: 10.1155/2013/385940
|View full text |Cite
|
Sign up to set email alerts
|

Thryroid Hormones and Hematological Indices Levels in Thyroid Disorders Patients at Moi Teaching and Referral Hospital, Western Kenya

Abstract: Problem Statement. Thyroid disorders are prevalent in western Kenya, but the effects of disorders on thyroid hormones and hematological indices levels have not been documented. Study Population. Patients treated for thyroid disorders at the MTRH between January 2008 and December 2011. Objectives. To determine the thyroid hormones and hematological indices levels in thyroid disorders patients at the MTRH, western Kenya. Methodology. A retrospective study in which patient data and stored samples of patients, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
41
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 15 publications
11
41
2
1
Order By: Relevance
“…The most prevalent hematological disorder with thyroiditis is anemia and it is indicated by a decrease in the number of RBCs and hemoglobin concentration. [8,11,13,16,19] The present report correlates with the aforementioned findings as a significant decrease was observed in the number of RBCs, hemoglobin concentration, PCV, and MCH between the thyroid disorder and normal thyroid groups and the prevalence of anemia increased by threefold with thyroid dysfunction compared with euthyroid females. Although anemia was reported with different types of thyroiditis, it is more common in hypothyroidism compared to hyperthyroidism.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The most prevalent hematological disorder with thyroiditis is anemia and it is indicated by a decrease in the number of RBCs and hemoglobin concentration. [8,11,13,16,19] The present report correlates with the aforementioned findings as a significant decrease was observed in the number of RBCs, hemoglobin concentration, PCV, and MCH between the thyroid disorder and normal thyroid groups and the prevalence of anemia increased by threefold with thyroid dysfunction compared with euthyroid females. Although anemia was reported with different types of thyroiditis, it is more common in hypothyroidism compared to hyperthyroidism.…”
Section: Discussionsupporting
confidence: 86%
“…Although anemia was reported with different types of thyroiditis, it is more common in hypothyroidism compared to hyperthyroidism. [3,7,8,11,14,16] The decreased prevalence of anemia with hyperthyroidism could be explained by the observed increase in erythrocytosis. [8,16] The current study supports the earlier observations as it showed a significant increase in the prevalence of anemia in the overt and occult hypothyroidism groups compared to normal thyroid group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations